Analisis kritis sistem evaluasi pendidikan Indonesia - Al Fajri, Taufiq Akbar; Novita, Evi Diyah; Dayana, Dayana; Rahayu, Anisa Agustina; Ramadhani, Aliffiah Elsa Fitri; Sembiring, Royhan Febriyanta; Kadir, Abdul (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2022)
This study aims to evaluate the Indonesian national education system that has existed Indonesia for decades. The assessment method used is a comparison with the national basis, the 1945 Constitution of the Republic of Indonesia (UUD RI 1945), and is aimed at Indonesia's national law on education systems and practices. The research method used is a literature study. The results of the study indicate that in an effort to advance the quality of students, a strategic, structured procedure system is needed in planning, organizing, evaluating processes, and making continuous improvements to the education system in Indonesia. One of the results of the evaluation of the education system is the change in the evaluation of student assessment from the National Examination (UN) to the Minimum Competency Assessment (Asessmen Kompetensi Minimum). This proves that the National Examination has not been fully effective in assessing the quality of students, so this Minimum Competency Assessment is an effective substitute because it measures the competence of reasoning used in solving problems in various contexts of teacher certification in improving teacher quality.